Exploring Classroom Environment as a Predominant Factor Affecting Students' Academic Performance in Lagos State Junior Secondary Schools, Nigeria - Akinyemi, Isiaka Adeniran; Gbesoevi, Emmanuel Semako; Afolabi, Sherifat Abimbola (Journal of Education and Learning Research, 2024)
This study was conducted to investigate the classroom environment as a predominant factor affecting students' academic performance in Lagos State junior secondary schools, Nigeria. A sample size of 250 students was drawn using both purposive and simple random sampling techniques. The instruments used for data collection were a questionnaire titled “Classroom Environment Questionnaire and tagged (CEQ),” whose reliability coefficient was found to be 0.85, and an achievement test to measure the students’ academic performance. Findings from the study revealed that there is a significant relationship between class size and students' academic performance in public junior secondary schools (r =.829), a significant relationship exists between instructional material usage and students' academic performance in public junior secondary schools (r =.745), a significant relationship exists between school climate and students' academic performance in public junior secondary schools (r =.775), and a significant relationship exists between classroom organization and students' academic performance in public junior secondary schools in Lagos State (r =.925). It was recommended that to ensure efficient service delivery, or the teaching-learning process, the government, through the Education Districts, pledge to supply junior secondary schools with economically improved and pertinent instructional resources, as this would enhance students’ academic performance in schools.